(The Effect on Temperature and Additing of Corn and Rice to the Quality of The Snack Food Made From By Product of Cracker) - Neffi Ridwan, Indra; T. Sutrisno, Ella; Supriatna, Dadang; Anita Rini, Hellen (Warta Industri Hasil Pertanian, 2004)
The research on the effect extrusion temperature and addition of corn and rice for the quality of the snack food made from by product of cracker has been conducted. The aim of the research was to study the possibility of use by product of the cracker in producing of the nutritious food product and to give more beneficial or advantage economically to the cracker by product. The research design was the completed randomize design factorially and replicated twice. The temperature variable treatments were 170 C and 180 C respectively, and the comparison of the cracker by product, corn and rice which were 85:10;5, 80:10:10, 75:10:15, 70:10:20, and 65:10:15 respectively. The results indicated that the product which has been made at 180 C extrusion temperature with the comparison of the material 70:10:20 was the best product in term of its characteristic on the linier expansion degree, degree of crispiness, moisture content, protein content, fat content, carbohydrate content and the hedonic test result.